Pesticide degradation in water using atmospheric air cold plasma. (February 2016) - Sarangapani, Chaitanya; Misra, N.N.; Milosavljevic, Vladimir; Bourke, Paula; O'Regan, Finbarr; Cullen, P.J.
Abstract: A high voltage dielectric barrier discharge plasma reactor using atmospheric air as the inducer gas was studied for the degradation of pesticides (dichlorvos, malathion, endosulfan) in water. The degradation kinetics of the pesticides were studied using GC–MS as a function of plasma control parameters. Electrical characterisation of the plasma revealed that the plasma discharge consisted of filamentary streamers. Excited nitrogen, reactive oxygen species and OH radicals generated in the dielectric barrier discharge (DBD) plasma reactor were identified using optical emission spectroscopy. Ozone, used as an indicator for metastable oxygen species, was quantified within the reactor at concentrations of 1600, 2200, 2800 ppm after 8 min of plasma treatment for applied voltages of 60, 70, and 80 kV respectively. The degradation efficacy of pesticides after 80 kV and 8 min of plasma treatment were found to be 78.98 ± 0.81% for dichlorvos, 69.62 ± 0.14% for malathion and 57.71 ± 0.58% for endosulfan. Degradation was found to follow first order kinetics. GC–MS analyses showed that the degraded compounds and intermediates formed were less toxic than the parent pesticide. A proposed mechanism of degradation of these pesticides is suggested.